Fostering Religious Moderation through English Debating at Tahfizul Quran Boarding School Context - Atin Kurniawati (Indonesian Journal of Islamic Education Studies (IJIES), 2022)
This article investigates the students' and teachers' perceptions of English debating and how English debating could foster religious moderation. This study employed a qualitative method with a narrative inquiry design in collecting the data in the form of stories from the members and the coach of an English debating club at a Tahfizul Quran boarding school senior high school. The data of this study were collected through semi-structured interviews with the English teacher, who also performed as the coach, and three former members of the club who had experienced one-year membership and had joined English debating competitions. The data were then analyzed using thematic coding to identify the themes from the data groups that correspond to the research questions and become the study's findings. The findings revealed that English debating had improved all students' English skills. As they were always triggered to build convincing arguments from different perspectives, they promoted their confidence to speak in public, critical and systematic thinking ability, and teamwork. English debating sometimes presented controversial issues against Islamic values and was troublesome for the students. Through English debating, they recognized that diversity and plurality existed, and at the same time, they could explore the universal values of Islam. English debating is beyond arguing pros and cons; it was a sequence that built many skills linguistically and non-linguistically.